Importance of organizational culture in the companies of the 21st century (2016)
This paper deals with the human talent as the fundamental basis of the functioning of organizations like the importance of having a clear and rooted in the organizational culture in the organization. Likewise strategies are generated to improve employee performance based on organizational culture, sense of belonging and different motivational factors that may contribute to the development of organizational objectives more efficiently and effectively, resulting in a better image organizations to clients-citizens.